The Osteoprotective and Chondroprotective Effects of Moringa oleifera: A Systematic Literature Review - Bagus Gede Krisna Astayogi; Kadek Gede Bakta Giri; I Gede Mahardika Putra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Bone and joint disorders, particularly arthritis and osteoporosis, represent significant global health burdens, often managed with NSAIDs and steroids, which carry potential systemic side effects. Moringa oleifera, a plant rich in bioactive compounds, has emerged as a potential therapeutic alternative due to its reported biological activities, including anti-inflammatory and antioxidant effects. This systematic review aimed to evaluate the existing preclinical evidence regarding the osteoprotective (bone-protective) and chondroprotective (cartilage-protective) effects of Moringa oleifera. Methods: A systematic literature search was conducted following PRISMA guidelines across PubMed, Science Direct, and Google Scholar databases for relevant English-language articles published between 2014 and 2024. Studies investigating the effects of Moringa oleifera extracts on bone or cartilage health in in vivo arthritis or bone defect models were included. Data on study design, intervention details, outcome measures, and key findings related to osteoprotection and chondroprotection were extracted and synthesized qualitatively. Results: Seven preclinical in vivo studies met the inclusion criteria. The included studies demonstrated that various extracts of Moringa oleifera (leaf ethanol, aqueous, methanol) exerted significant anti-inflammatory effects, evidenced by reduced paw edema, lower arthritis scores, and decreased inflammatory markers like CRP. Anti-nociceptive effects were also observed. Chondroprotective effects were indicated by improved radiographic scores (reduced joint space narrowing), cartilage regeneration, reduced fibrillation, and preservation of chondrocytes in histopathological analyses. Osteoprotective effects included increased osteoblast numbers, improved trabecular bone microarchitecture, decreased osteoclast numbers, reduced bone resorption, and enhanced bone healing, particularly when combined with marine collagen. Conclusion: Preclinical evidence strongly suggested that Moringa oleifera possesses significant osteoprotective and chondroprotective properties, mediated likely through its anti-inflammatory, anti-nociceptive, antioxidant, and direct cellular effects on bone and cartilage cells. Moringa oleifera holds potential as a supplementary or alternative therapeutic strategy for managing bone and joint diseases like arthritis and osteoporosis, although further rigorous clinical investigation is warranted.